Technology, application and potential of dynamic breast thermography for the detection of breast cancer. (March 2019) - Gonzalez-Hernandez, Jose-Luis; Recinella, Alyssa N.; Kandlikar, Satish G.; Dabydeen, Donnette; Medeiros, Lori; Phatak, Pradyumna
Highlights: An overview dynamic infrared thermography is presented. Clinical examinations using dynamic thermography are reviewed. Numerical simulations using cold stresses for breast cancer detection are reviewed. Role of Artificial intelligence in breast cancer diagnosis is reviewed. Possible future directions for breast cancer detection are discussed. Abstract: Early breast cancer detection improves the chances of survival, increases the options for curative treatment and helps reduce costs. There are a variety of screening techniques available to detect breast cancer such as mammography, magnetic resonance imaging and ultrasound. However, their sensitivities and specificities are suboptimal, especially in breasts with dense tissue. Infrared breast thermography is an adjunct screening technique that has been associated with the detection of early signs of breast cancer. However, its success has been limited. Dynamic infrared thermography was introduced to improve the detection of breast cancer and reduce the false positive and false negative rates. This works reviews the different modalities of dynamic infrared thermography, their advantages, shortcomings and opportunities for future development. This paper also covers recent advances, suggestions and possible directions for future work in the fields of numerical simulations, automatic feature identification and artificial intelligence for improving the detection of breast cancer using dynamic infrared thermography.